Composite positive electrode active material and preparation method and application thereof
By covering the surface of the lithium-rich manganese-based positive electrode material with cation disordered oxide shell to form a composite positive electrode active material, the problem of insufficient performance of the lithium-rich manganese-based positive electrode material in lithium-ion batteries is solved, and the battery's high efficiency and long life are achieved.
Patent Information
- Application Number
- CN202411999034.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Lithium-rich manganese-based positive electrode materials have problems with poor first-time Coulomb efficiency, rate performance and cycle performance in lithium-ion batteries.
A composite cathode active material is used, which consists of a lithium-rich manganese-based cathode material as the core and is coated on its surface. The cation cathode oxide includes a compound of a specific chemical composition and has the composite properties of a layered structure and spinel structure.
It effectively improves the first-time Coulomb efficiency, cycle performance and rate performance of the battery, and improves the transmission efficiency and structural stability of lithium ions.
Smart Images

Figure CN119812269A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries and relates to a composite positive electrode active material, in particular to a composite positive electrode active material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices, power tools, electric bicycles, electric vehicles, aerospace, energy storage systems and other fields due to their high energy density, voltage platform, cycle life, fast charging capability, no memory effect, wide operating temperature range, and environmental protection and renewable advantages. With the continuous expansion of application fields, higher requirements are put forward for the energy density of lithium-ion batteries.
[0003] As one of the important components of lithium-ion batteries, positive electrode active materials play a key role in improving battery energy density. Among the many positive electrode active materials, lithium-rich manganese-based positive electrode materials can cycle between 2.0V and 4.8V and have a high reversible capacity (not less than 300mAh·g -1 ) and energy density (not less than 900Wh·kg -1 ); however, lithium-rich manganese-based cathode materials generally have problems with poor first coulombic efficiency, rate performance and cycle performance.
[0004] Therefore, it is necessary to further improve the lithium-rich manganese-based positive electrode materials to enhance their first coulombic efficiency, rate performance and cycle performance. Summary of the invention
[0005] In view of the above-mentioned defects, the present invention provides a composite positive electrode active material, which has a high ion migration rate and electronic conductivity and good structural stability. Therefore, the composite positive electrode active material can effectively improve the first coulombic efficiency, rate performance and cycle performance of the battery.
[0006] The present invention also provides a method for preparing the composite positive electrode active material. The composite positive electrode active material prepared by the preparation method can effectively improve the first coulombic efficiency, rate performance and cycle performance of the battery.
[0007] The present invention also provides a method for preparing the composite positive electrode active material. The composite positive electrode active material prepared by the preparation method can effectively improve the first coulombic efficiency, rate performance and cycle performance of the battery.
[0008] The present invention also provides a positive electrode sheet, comprising the composite positive electrode active material or the composite positive electrode active material prepared by the preparation method. Therefore, the positive electrode sheet is used in a lithium-ion battery to effectively improve the first coulombic efficiency, rate performance and cycle performance of the battery.
[0009] The present invention also provides a lithium ion battery, comprising the composite positive electrode active material, or the composite positive electrode active material prepared by the preparation method, or the positive electrode sheet. Therefore, the battery has high first coulomb efficiency, rate performance and cycle performance.
[0010] A first aspect of the present invention provides a composite positive electrode active material, the composite positive electrode active material comprising a core and a shell layer coated on at least a portion of the surface of the core; the core comprises a lithium-rich manganese-based positive electrode material, the shell layer comprises a cationic disordered oxide; the cationic disordered oxide comprises a compound with a chemical composition shown in Formula 1,
[0011] Li z A x B 1-x O 2-y D y Formula 1
[0012] In formula 1, 0.90≤x<1.0, 0≤y≤0.2, 0.78<z<1.1, A includes Ni and Mn in a molar ratio of (0.6-1):1, B includes at least one of Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce, and D includes F and / or S;
[0013] In the X-ray diffraction spectrum of the cationic disordered oxide, there is a diffraction peak with 2θ of 63° to 66°, and the diffraction peak is a single peak without splitting.
[0014] The composite positive electrode active material as described above, wherein the mass ratio of the cationic disordered oxide to the lithium-rich manganese-based positive electrode material is (0.5-3):100.
[0015] The composite positive electrode active material as described above, wherein the thickness of the shell layer is 5 nm to 20 nm.
[0016] The composite positive electrode active material as described above, wherein the lithium-rich manganese-based positive electrode material comprises a compound having a chemical composition shown in Formula 2,
[0017] Li 1+m Ni a Mn b M c O 2+m-d N d Formula 2
[0018] In formula 2, 0.2≤m≤0.4, a+b+c=1, 0.42≤a / b≤0.67, 0≤c≤0.02, 0≤d≤0.02; M includes at least one of Na, Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce; and N includes at least one of S, F, and P.
[0019] The second aspect of the present invention provides a method for preparing the composite positive electrode active material of the first aspect, comprising the following steps:
[0020] In an oxygen atmosphere, a first raw material including a lithium source, a source A, a source B, and a source D is uniformly mixed and then sequentially subjected to a first sintering and a second sintering to obtain a cationic disordered oxide; wherein the temperature of the first sintering is 300 to 400° C., and the holding time is 2 to 4 hours; the temperature of the second sintering is 450 to 600° C., and the holding time is 10 to 40 hours; the cationic disordered oxide includes a compound with a chemical composition shown in Formula 1,
[0021] Li z A x B 1-x O 2-y D y Formula 1
[0022] In formula 1, 0.90≤x<1.0, 0≤y≤0.2, 0.78<z<1.1, A includes Ni and Mn in a molar ratio of (0.6-1):1, B includes at least one of Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce, and D includes F and / or S;
[0023] In the X-ray diffraction spectrum of the cationic disordered oxide, there is a diffraction peak with a 2θ of 63° to 66°, and the diffraction peak is a single peak without splitting;
[0024] In an oxygen atmosphere, the second raw material including the cationic disordered oxide and the lithium-rich manganese-based positive electrode material is uniformly mixed and then subjected to a third sintering to obtain the composite positive electrode active material; wherein the third sintering temperature is 300-500° C. and the insulation time is 2-12 hours.
[0025] The method for preparing the composite positive electrode active material as described above, wherein the lithium-rich manganese-based positive electrode material is prepared by the following method:
[0026] The raw materials including nickel manganese precursor, lithium source, M source and N source are mixed to obtain a mixed material; the mixed material is sintered at 700-1100° C. for 10-24 hours in an oxygen atmosphere to obtain the lithium-rich manganese-based positive electrode material.
[0027] The third aspect of the present invention provides a method for preparing the composite positive electrode active material of the first aspect, comprising the following steps:
[0028] In an oxygen atmosphere, a lithium-rich manganese-based positive electrode material is uniformly mixed with raw materials including a lithium source, a source A, a source B and a source D, and then a first sintering and a second sintering are performed in sequence to obtain a composite positive electrode active material; wherein the temperature of the first sintering is 300-400° C., and the insulation time is 3-8 hours; the temperature of the second sintering is 450-700° C., and the insulation time is 20-40 hours;
[0029] The composite positive electrode active material comprises a core and a shell layer covering at least a portion of the surface of the core; the core comprises a lithium-rich manganese-based positive electrode material, and the shell layer comprises a cationic disordered oxide; the cationic disordered oxide comprises a compound with a chemical composition shown in Formula 1,
[0030] Li z A x B 1-x O 2-y D y Formula 1
[0031] In formula 1, 0.90≤x<1.0, 0≤y≤0.2, 0.78<z<1.1, A includes Ni and Mn in a molar ratio of (0.6-1):1, B includes at least one of Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce, and D includes F and / or S;
[0032] In the X-ray diffraction spectrum of the cationic disordered oxide, there is a diffraction peak with 2θ of 63° to 66°, and the diffraction peak is a single peak without splitting.
[0033] The method for preparing the composite positive electrode active material as described above, wherein the lithium-rich manganese-based positive electrode material is prepared by the following method:
[0034] The raw materials including nickel manganese precursor, lithium source, M source and N source are mixed to obtain a mixed material; the mixed material is sintered at 700-1100° C. for 10-24 hours in an oxygen atmosphere to obtain the lithium-rich manganese-based positive electrode material.
[0035] A fourth aspect of the present invention provides a positive electrode sheet, comprising the composite positive electrode active material of the first aspect, or the composite positive electrode active material prepared by the preparation method of the second aspect, or the composite positive electrode active material prepared by the preparation method of the third aspect.
[0036] The fifth aspect of the present invention provides a lithium-ion battery, which includes the composite positive electrode active material of the first aspect, or the composite positive electrode active material prepared by the preparation method of the second aspect, or the composite positive electrode active material prepared by the preparation method of the third aspect, or the positive electrode sheet of the fourth aspect.
[0037] The composite positive electrode active material of the present invention includes a lithium-rich manganese-based positive electrode material with a core and a cationic disordered oxide coated on at least part of the surface of the core. In the XRD of the cationic disordered oxide, there is a single peak without splitting at 2θ of 63° to 66°, indicating that the material contains both a layered structure and a spinel structure, wherein the layered structure can effectively improve the compatibility between the core and the shell, thereby improving the transmission efficiency of lithium ions; the spinel structure has a high structural stability under high voltage, and the two cooperate with each other to effectively improve the ion diffusion capacity and structural stability of the positive electrode material. At the same time, the relative content of nickel and manganese in the cationic disordered oxide is relatively appropriate, which can make the cationic disordered oxide have both good electrochemical properties and structural stability. Therefore, the composite positive electrode active material can effectively improve the first coulombic efficiency, cycle performance and rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a SEM image of the composite positive electrode active material in Example 1 of the present invention;
[0039] Figure 2 This is a SEM image of the composite positive electrode active material in Comparative Example 1 of the present invention;
[0040] Figure 3 The cationic disordered oxide in Example 1 of the present invention and the typical ternary layered LiNi 0.5 Mn 0.5 O2 and typical spinel LiNi 0.5 Mn 1.5 Comparison of local XRD diffraction peaks of O4 at 2θ of 63° to 66°;
[0041] Figure 4 The cationic disordered oxide in Comparative Example 2 of the present invention and the typical ternary layered LiNi 0.5 Mn 0.5 O2 and typical spinel LiNi 0.5 Mn 1.5 Comparison of local XRD diffraction peaks of O4 at 2θ of 63° to 66°;
[0042] Figure 5 The cationic disordered oxides in Comparative Examples 5 and 6 of the present invention and the typical ternary layered LiNi 0.5 Mn 0.5 O2 and typical spinel LiNi0.5 Mn 1.5 Comparison of local XRD diffraction peaks of O4 at 2θ of 63° to 66°;
[0043] Figure 6 is a charge and discharge curve diagram of the battery at 1C in Example 1 of the present invention;
[0044] Figure 7 is a charge and discharge curve diagram of the battery at 1C in Example 3 of the present invention;
[0045] Figure 8 is a charge and discharge curve diagram of the battery at 1C in Example 14 of the present invention;
[0046] Fig. 9 1 is a charge and discharge curve of the battery in Example 15 of the present invention at 1C. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Lithium-rich manganese-based cathode materials have high energy density (discharge capacity can reach 250mAh g -1 The advantages of high voltage characteristics (voltage window of 2.0-4.8V), high safety and low cost make it stand out among many cathode active materials, with broad application prospects, and it is one of the hot spots in the current battery research. However, since lithium-rich manganese-based cathode materials have high interfacial reaction activation energy, it is often necessary to activate the Li2MnO3 component under high voltage; and during the cyclic charge and discharge process under high voltage, it is often accompanied by the irreversible escape of lattice oxygen, which will lead to irreversible changes in the structure of the cathode material, making it impossible for some lithium ions to be smoothly embedded in the material during the discharge process; on the other hand, the escaped active oxygen will react with Li in the electrolyte. + When a reaction occurs, the generated by-products will adhere to the surface of the material and increase the internal resistance of the battery, thereby causing a decrease in the battery's first coulombic efficiency, cycle performance and rate performance.
[0049] At present, the surface of lithium-rich manganese-based positive electrode materials is generally coated to inhibit the escape of lattice oxygen, avoid direct contact between the material and the electrolyte, inhibit the occurrence of side reactions between the electrolyte and the material, and thus improve the first coulombic efficiency, cycle performance and rate performance of the battery. However, the coating materials used in the prior art are generally elemental carbon, metal oxides (such as Al2O3, ZrO2, MgO,) or metal fluorides (such as MgF2, AlF3, CeF3), which are not electrochemically active and will affect the transmission efficiency of lithium ions, which is not only not conducive to the rate performance of the battery, but also significantly reduces the mass energy density of the positive electrode material, limiting the improvement of the comprehensive performance of the positive electrode material.
[0050] The inventors found that using cationic disordered oxides as coating materials can effectively inhibit the escape of lattice oxygen in lithium-rich manganese-based positive electrode materials and improve their structural stability; at the same time, the anions in the cationic disordered oxides undergo redox reactions under high voltages and can participate in charge compensation, which is beneficial to improving the discharge capacity of the positive electrode material without causing a loss of energy density; and the oxygen atoms in the material are densely packed structures and are not easy to escape, which can further reduce the oxygen evolution problem and help to enhance the overall structural stability of the composite positive electrode active material to a certain extent.
[0051] However, the inventors have found that the existing cationic disordered oxides contain more metal elements and have a more complex composition, which makes their crystal structure more complex and cannot be well compatible with the matrix material, the lithium-rich manganese-based positive electrode material, which hinders the transmission of lithium ions and affects the rate performance of the battery. Therefore, it is necessary to optimize the structure of the cationic disordered oxide to improve the compatibility between the coating layer and the core, thereby improving the migration efficiency of lithium ions.
[0052] Based on the above analysis, the inventors found that the structure of lithium-rich manganese-based positive electrode materials is usually a layered structure. If the compatibility of cationic disordered oxides with lithium-rich manganese-based positive electrode materials is to be improved, it is an effective method to include a layered structure in the cationic disordered oxide. However, the cationic disordered oxides with layered structures have poor structural stability under high voltages, which will affect the overall structural stability of the positive electrode active material and have a negative impact on the cycle performance of the battery. Since some tetrahedral sites and octahedral sites in the spinel structure are coplanar, interconnected three-dimensional ion diffusion channels can be formed, which is not only conducive to lithium ion deintercalation, but also can reduce the electrostatic repulsion during lithium deintercalation, and can effectively inhibit the transformation of crystal phases under high voltages. Therefore, the lattice expansion and volume strain of the spinel structure are small under high voltage, and it has high structural stability.
[0053] Based on the above analysis, it can be considered that when the cationic disordered oxide includes both a layered structure and a spinel structure, it can not only improve the compatibility of the cationic disordered oxide with lithium-rich manganese-based positive electrode materials, but also ensure the structural stability of the cationic disordered oxide under high voltage.
[0054] In the X-ray diffraction spectrum, lithium nickel manganese oxide (such as LiNi 0.5 Mn 0.5 O2) has two diffraction peaks at 2θ of 63°~66°, and lithium nickel manganese oxide (such as LiNi) with a typical spinel structure 0.5 Mn 1.5 O4) has a sharp split peak at 2θ of 63°~66°; when the characteristic peak of the cationic disordered oxide at 2θ of 63°~66° is a single peak without splitting and in the shape of a steamed bun, it indicates that its internal crystal is not a single layered structure or spinel structure, but a composite material with two structures coexisting.
[0055] From this, it can be inferred that when there is a diffraction peak with 2θ of 63°~66° in the X-ray diffraction spectrum of the cationic disordered oxide, and the diffraction peak is a single peak without splitting, there are both layered structure and spinel structure in the crystals inside the material, which can effectively improve the lithium ion transmission efficiency of the positive electrode active material and the structural stability under high voltage.
[0056] However, it is also necessary to control the proportion of spinel structure in cationic disordered oxides. When the proportion of spinel structure is large, Mn dissolution is likely to occur during the cycle, resulting in capacity decay; and there is a negative impact on the ion migration rate and electronic conductivity of the oxide, which is not conducive to the improvement of the discharge capacity and rate of the battery.
[0057] The inventors further discovered that the relative contents of nickel and manganese in the cationic disordered oxide have a great influence on its structure. When there is too little nickel and too much manganese, the overall structure of the oxide will change to a spinel structure; when there is too much nickel and too little manganese, the crystal structure of the oxide will be dislocated, which will hinder the deintercalation of lithium ions and affect the electrochemical properties of the material. Therefore, the inventors tried to control the relative contents of nickel and manganese in the cationic disordered oxide to adjust the structure of the cationic disordered oxide so that the cationic disordered oxide contains a layered structure to enhance the compatibility of the coating layer with the core, and to have both good electrochemical properties and structural stability.
[0058] Based on the above analysis, the first aspect of the present invention provides a composite positive electrode active material, which includes a core and a shell layer covering at least a portion of the surface of the core; the core includes a lithium-rich manganese-based positive electrode material, and the shell layer includes a cationic disordered oxide; the cationic disordered oxide includes a compound with a chemical composition shown in Formula 1,
[0059] Li z A x B 1-x O 2-y D y Formula 1
[0060] In formula 1, 0.90≤x<1.0, 0≤y≤0.2, 0.78<z<1.1, A includes Ni and Mn in a molar ratio of (0.6-1):1, B includes at least one of Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce, and D includes F and / or S;
[0061] In the X-ray diffraction spectrum of the cationic disordered oxide, there is a diffraction peak with 2θ of 63° to 66°, and the diffraction peak is a single peak without splitting.
[0062] Illustratively, the molar ratio of Ni to Mn in the cationic disordered oxide is 0.6:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1, or 1:1.
[0063] It should be noted that, when B includes multiple specific elements of the aforementioned elements at the same time, the present invention does not specifically limit the ratio between the specific elements; when D includes multiple specific elements of the aforementioned elements at the same time, the present invention does not specifically limit the ratio between the specific elements.
[0064] The present invention does not specifically limit the chemical composition of the lithium-rich manganese-based positive electrode material, which can be selected conventionally in the art; and the present invention does not specifically limit the source of the lithium-rich manganese-based positive electrode material, which can be a commercially available product or a product prepared by a conventional preparation method familiar to those skilled in the art.
[0065] The present invention does not specifically limit the source of the cationic disordered oxide, and can use commercially available products or products prepared by conventional preparation methods familiar to those skilled in the art. It is only necessary that the chemical composition of the cationic disordered oxide satisfies Formula 1, and in its X-ray diffraction spectrum, there is a diffraction peak with a 2θ value of 63° to 66°, and the diffraction peak is a single peak without splitting.
[0066] The composite positive electrode active material in the present invention uses a lithium-rich manganese-based positive electrode material as a core and a cationic disordered oxide as a coating shell, which can effectively inhibit the escape of lattice oxygen in the lithium-rich manganese-based positive electrode material and improve the structural stability of the lithium-rich manganese-based positive electrode material; at the same time, the cationic disordered oxide can also be used as an active substance to participate in electrochemical reactions under high voltage, which is beneficial to improving the discharge capacity of the positive electrode material without causing a loss of energy density; and because the oxygen atoms in the material are in a densely packed structure and are not easy to escape, it has a higher structural stability and can improve the overall structural stability of the composite positive electrode active material.
[0067] At the same time, there is a characteristic peak at 2θ of 63° to 66° in the X-ray diffraction spectrum of the cationic disordered oxide in the present invention, and it is a single peak without splitting, indicating that the material contains both a layered structure and a spinel structure, wherein the layered structure can effectively improve the compatibility of the cationic disordered oxide with the lithium-rich manganese-based positive electrode material, thereby improving the transmission efficiency of lithium ions; the spinel structure can constitute an interconnected three-dimensional ion diffusion channel, which is not only conducive to the deintercalation of lithium ions, but also can reduce the electrostatic repulsion during lithium deintercalation, and its lattice expansion and volume strain are small at high voltage, and it has a high structural stability; the two work together to effectively improve the lithium ion transmission efficiency and structural stability of the positive electrode active material. Moreover, the present invention controls the relative content of nickel and manganese in the cationic disordered oxide, so that the nickel and manganese content therein is more appropriate, avoiding too much spinel structure caused by too little nickel and too much manganese, and dislocation of the crystal structure caused by too much nickel and too little manganese, thereby making the cationic disordered oxide have both good electrochemical properties and structural stability.
[0068] In addition, when the cationic disordered oxide is doped with F and S, the F has a stronger electronegativity than O and can form a more stable bond with the cation; S can provide electrons to the lattice oxygen at high voltage to prevent oxidation, which can further improve the structural stability of the cationic disordered oxide, thereby improving the structural stability of the composite positive electrode active material and enabling the battery to have higher cycle performance.
[0069] Therefore, the composite positive electrode active material in the present invention can effectively improve the first coulombic efficiency, cycle performance and rate performance of the battery.
[0070] Furthermore, the mass ratio of cationic disordered oxides and lithium-rich manganese-based positive electrode materials in the composite positive electrode active material also has a great influence on the first coulombic efficiency, cycle performance and rate performance of the battery.
[0071] In a specific embodiment, the mass ratio of the cationic disordered oxide to the lithium-rich manganese-based positive electrode material is (0.5-3): 100. Within this range, not only can the structural stability and ion transport capacity of the composite positive electrode active material be effectively improved, but also excessive cationic disordered oxides can be prevented from hindering the migration of lithium ions, thereby further improving the first coulombic efficiency, cycle performance and rate performance of the battery.
[0072] Exemplarily, the mass ratio of the cationic disordered oxide to the lithium-rich manganese-based positive electrode material is 0.5:100, 1:100, 1.5:100, 2:100, 2.5:100 or 3:100.
[0073] Furthermore, the thickness of the shell will also have a certain impact on the battery's initial coulombic efficiency, cycle performance and rate performance. If the shell is too thin, it will not be able to effectively isolate the electrolyte from the lithium-rich manganese-based cathode material in the core, leading to side reactions; if the shell is too thick, the lithium ion migration path will become longer, affecting the lithium ion migration efficiency.
[0074] In a specific embodiment, the thickness of the shell layer is 5nm to 20nm. Within this range, the occurrence of side reactions between the electrolyte and the lithium-rich manganese-based positive electrode material can be effectively suppressed, and at the same time, the shell layer will not be too thick, which is conducive to the smooth transmission of lithium ions, thereby further improving the first coulombic efficiency, cycle performance and rate performance of the battery.
[0075] Exemplarily, the thickness of the shell layer is 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm or 20 nm.
[0076] The "shell thickness" in the present invention can be obtained by transmission electron microscopy (TEM) testing.
[0077] Furthermore, the lithium-rich manganese-based positive electrode material can also be doped to further improve the structural stability of the composite positive electrode active material. In one embodiment, the structural stability of the lithium-rich manganese-based positive electrode material can be improved by doping with metal cations (such as at least one of Na, Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce); wherein the metal cation can form a higher bond energy with the oxygen in the lithium-rich manganese-based positive electrode material, thereby inhibiting the escape of lattice oxygen and improving its structural stability. In another embodiment, the lattice oxygen in the lithium-rich manganese-based positive electrode material can also be stabilized by doping with anions (such as at least one of S, F, and P), which plays a role in improving the structural stability.
[0078] In a specific embodiment, the lithium-rich manganese-based positive electrode material includes a compound with a chemical composition shown in Formula 2,
[0079] Li 1+m Ni a Mn b M c O 2+m-d N d Formula 2
[0080] In formula 2, 0.2≤m≤0.4, a+b+c=1, 0.42≤a / b≤0.67, 0≤c≤0.02, 0≤d≤0.02; M includes at least one of Na, Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce; and N includes at least one of S, F, and P.
[0081] At this time, the lithium-rich manganese-based positive electrode material has higher structural stability, which can further improve the battery's first coulombic efficiency, cycle performance and rate performance.
[0082] It should be noted that, when M includes multiple specific elements of the aforementioned elements at the same time, the present invention does not specifically limit the ratio between the specific elements; when N includes multiple specific elements of the aforementioned elements at the same time, the present invention does not specifically limit the ratio between the specific elements.
[0083] The second aspect of the present invention provides a method for preparing the composite positive electrode active material of the first aspect, comprising the following steps:
[0084] In an oxygen atmosphere, a first raw material including a lithium source, a source A, a source B, and a source D is uniformly mixed and then subjected to a first sintering and a second sintering to obtain a cationic disordered oxide; wherein the temperature of the first sintering is 300 to 400° C., and the holding time is 2 to 4 hours; the temperature of the second sintering is 450 to 600° C., and the holding time is 10 to 40 hours; the cationic disordered oxide includes a compound with a chemical composition shown in Formula 1,
[0085] Li z A x B 1-x O 2-y D y Formula 1
[0086] In formula 1, 0.90≤x<1.0, 0≤y≤0.2, 0.78<z<1.1, A includes Ni and Mn in a molar ratio of (0.6-1):1, B includes at least one of Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce, and D includes F and / or S;
[0087] In the X-ray diffraction spectrum of the cationic disordered oxide, there is a diffraction peak with 2θ of 63° to 66°, and the diffraction peak is a single peak without splitting;
[0088] In an oxygen atmosphere, a second raw material including a cationic disordered oxide and a lithium-rich manganese-based positive electrode material is uniformly mixed and then subjected to a third sintering to obtain a composite positive electrode active material; wherein the third sintering temperature is 300-500° C. and the insulation time is 2-12 hours.
[0089] Specifically, in an oxygen atmosphere, raw materials including a lithium source, a source A, a source B and a source D are uniformly mixed to obtain a first raw material; the first raw material is subjected to a first sintering at a temperature of 300 to 400° C., and the holding time is 2 to 4 hours; then the product obtained after the first sintering is subjected to a second sintering at 450 to 600° C., and the holding time is 10 to 40 hours. After the sintering, a cationic disordered oxide is obtained; the cationic disordered oxide includes a compound with a chemical composition shown in Formula 1, and in the X-ray diffraction spectrum of the cationic disordered oxide, there is a diffraction peak with 2θ of 63° to 66°, and the diffraction peak is a single peak without splitting;
[0090] The raw materials including the cationic disordered oxide prepared above and the lithium-rich manganese-based positive electrode material are uniformly mixed according to a set mass ratio to obtain a second raw material; the second raw material is subjected to a third sintering at a temperature of 300-500°C in an oxygen atmosphere for a holding time of 2-12 hours; during this process, the coating material cationic disordered oxide is coated on at least a portion of the surface of the lithium-rich manganese-based positive electrode material to prepare a composite positive electrode active material.
[0091] Illustratively, the first sintering temperature is 300° C., 320° C., 340° C., 360° C., 380° C. or 400° C.; and the holding time is 2 h, 2.5 h, 3 h, 3.5 h or 4 h.
[0092] Illustratively, the second sintering temperature is 450°C, 475°C, 500°C, 525°C, 550°C, 575°C or 600°C; and the holding time is 10h, 15h, 20h, 25h, 30h, 35h or 40h.
[0093] Exemplarily, the temperature of the third sintering is 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C or 500°C; and the holding time is 2h, 4h, 6h, 8h, 10h or 12h.
[0094] The present invention does not specifically limit the source of the lithium-rich manganese-based positive electrode material, and a commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.
[0095] The "oxygen atmosphere" in the present invention refers to an atmosphere containing oxygen. The present invention does not specifically limit the volume content of oxygen in the atmosphere. For example, sintering can be carried out in an air atmosphere or an oxygen atmosphere.
[0096] It should be noted that during the first sintering, the temperature is raised from room temperature to the temperature required for the first sintering; after the first sintering is completed, the temperature is directly raised to the temperature required for the second sintering for the second sintering; during the third sintering, the product obtained after the second sintering needs to be cooled to room temperature and then mixed with the lithium-rich manganese-based positive electrode material for the third sintering.
[0097] The present invention does not specifically limit the heating rates during the first sintering, the second sintering and the third sintering, and a suitable heating rate can be selected according to actual conditions. For example, the heating rate can be 2 to 10°C.
[0098] The lithium source in the present invention refers to a raw material for providing the Li element, the A source refers to a raw material for providing the A element (Ni element and Mn element), the B source refers to a raw material for providing the B element (Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, Ce at least one), and the D source refers to a raw material for providing the D element (F and / or S). As long as the target element (Li element, A element, B element, D element) is contained, it belongs to the limitation of the present invention, and a target element can be introduced into the reaction system through one or more raw materials. It should be explained that when the raw material includes two or more elements of the target element at the same time, the raw material can be understood as the element source of the two target elements.
[0099] Exemplarily, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium sulfate, lithium chloride and lithium fluoride; the A source includes a nickel source and a manganese source, wherein the nickel source includes at least one of nickel oxide, carbonate, hydroxide and oxalate, for example, nickel oxide (NiO), nickel carbonate (NiCO3), nickel hydroxide (Ni(OH)2), and nickel oxalate (NiC2O4); the manganese source includes at least one of manganese oxide, carbonate, hydroxide and oxalate, for example, manganese tetraoxide (Mn3O4), manganese carbonate (MnCO3), manganese hydroxide (Mn(OH)2), and manganese oxalate (MnC2O4); the B source includes B element At least one of the corresponding oxides, hydroxides and carbonates, for example, including at least one of strontium oxide (SrO), yttrium oxide (Y2O3), titanium dioxide (TiO2), zirconium oxide (ZrO2), niobium pentoxide (Nb2O5), tantalum oxide (Ta2O5), chromium trioxide (Cr2O3), molybdenum trioxide (MoO3), tungsten trioxide (WO3), aluminum oxide (Al2O3), tin oxide (SnO2), antimony oxide (Sb2O5), tellurium oxide (TeO2), cerium oxide (CeO2), lanthanum hydroxide (La(OH)3), cobalt hydroxide (Co(OH)2), and magnesium carbonate (MgCO3); the D source can be a sulfide and / or a fluoride.
[0100] The present invention does not specifically limit the sources of the lithium source, source A, source B, and source D, and commercially available products or products prepared by conventional preparation methods well known to those skilled in the art may be used.
[0101] The present invention does not specifically limit the molar ratio of the lithium source, source A, source B, and source D. It is only necessary that the chemical composition of the prepared cationic disordered oxide satisfies Formula 1 and that there is an unsplit single peak at 2θ of 63° to 66° in its X-ray diffraction spectrum.
[0102] The present invention does not specifically limit the mass ratio of the cationic disordered oxide to the lithium-rich manganese-based positive electrode material; further, by controlling the mass ratio between the two, the mass ratio of the cationic disordered oxide to the lithium-rich manganese-based positive electrode material in the prepared composite positive electrode active material can be (0.5-3):100.
[0103] The present invention does not specifically limit the mixing method, and the mixing can be carried out by conventional methods in the art, as long as the raw materials are mixed uniformly. For example, the mixing can be carried out by a high-speed mixer.
[0104] The preparation method of the composite positive electrode active material in the present invention first prepares a cationic disordered oxide by a special method. The material has a chemical composition shown in Formula 1, and in its XRD spectrum, there is a single peak without splitting at 2θ of 63° to 66°, indicating that the material has both a layered structure and a spinel structure. The material is used as a coating material to coat the surface of a lithium-rich manganese-based positive electrode material, which can effectively improve the compatibility of the cationic disordered oxide with the lithium-rich manganese-based positive electrode material, thereby improving the migration efficiency of lithium ions. The coating layer can also inhibit the side reaction of the lithium-rich manganese-based positive electrode material with the electrolyte, thereby effectively inhibiting the escape of lattice oxygen and improving the structural stability of the positive electrode material; the cationic disordered oxide can also be used as an active substance, which is conducive to improving the discharge capacity of the positive electrode material and reducing the loss of energy density. At the same time, the spinel structure can form interconnected three-dimensional ion diffusion channels, which is not only conducive to the deintercalation of lithium ions, but also can reduce the electrostatic repulsion during lithium deintercalation. Under high voltage, its lattice expansion and volume strain are small, and it has high structural stability; the two work together to effectively improve the lithium ion transmission efficiency and structural stability of the positive electrode active material. In addition, the relative content of nickel and manganese in the cationic disordered oxide is relatively appropriate, which can effectively avoid the excessive spinel structure caused by too little nickel and too much manganese, and the dislocation of the crystal structure caused by too much nickel and too little manganese, thereby making the cationic disordered oxide have both good electrochemical properties and structural stability.
[0105] Therefore, the composite positive electrode active material prepared by the above preparation method can effectively improve the first coulombic efficiency, cycle performance and rate performance of the battery.
[0106] In a specific embodiment, the lithium-rich manganese-based positive electrode material is prepared by the following method:
[0107] The raw materials including nickel manganese precursor, lithium source, M source and N source are mixed to obtain a mixed material; the mixed material is sintered at 700-1100° C. for 10-24 hours in an oxygen atmosphere to obtain a lithium-rich manganese-based positive electrode material.
[0108] The lithium-rich manganese-based positive electrode material prepared by the above preparation method is doped with M element (at least one of Na, Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce) and N element (at least one of S, F, and P), thereby further improving the structural stability of the lithium-rich manganese-based positive electrode material.
[0109] Exemplarily, the sintering temperature is 700°C, 800°C, 900°C, 1000°C or 1100°C; and the holding time is 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.
[0110] The present invention does not specifically limit the chemical composition of the nickel-manganese precursor, and conventional materials in the art may be used; for example, it may be one or more of nickel-manganese oxides, carbonates, hydroxides, and oxalates; the present invention does not specifically limit the source of the nickel-manganese precursor, and commercially available products or products prepared by conventional preparation methods well known to those skilled in the art may be used.
[0111] The M source in the present invention refers to a raw material for providing the M element, and the M element includes at least one of Na, Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce. The N source refers to a raw material for providing the N element, and the N element includes at least one of S, F, and P. As long as the aforementioned target elements (Li, M, and N) are contained, they are within the scope of the present invention. Exemplarily, the M source may be at least one of the oxides, hydroxides, and carbonates of the aforementioned metal elements; the N source may be at least one of the sulfides, fluorides, and phosphates.
[0112] The present invention does not specifically limit the sources of the M source and the N source, and commercially available products or products prepared by conventional preparation methods well known to those skilled in the art may be used.
[0113] The present invention does not specifically limit the molar ratio of the nickel-manganese precursor material, the lithium source, the M source and the N source; further, the prepared lithium-rich manganese-based positive electrode material can satisfy Formula 2 by controlling the molar ratio between the four.
[0114] The present invention does not impose any specific limitation on the heating rate during the sintering process, and a suitable heating rate may be selected according to actual conditions, for example, the heating rate may be 2 to 10° C. / min.
[0115] A third aspect of the present invention provides a method for preparing a composite positive electrode active material, comprising the following steps:
[0116] In an oxygen atmosphere, a lithium-rich manganese-based positive electrode material is uniformly mixed with raw materials including a lithium source, a source A, a source B and a source D, and then a first sintering and a second sintering are performed in sequence to obtain a composite positive electrode active material; wherein the first sintering temperature is 300-400° C., and the heat preservation time is 3-8 hours; the second sintering temperature is 450-700° C., and the heat preservation time is 20-40 hours;
[0117] The composite positive electrode active material comprises a core and a shell layer covering at least a portion of the surface of the core; the core comprises a lithium-rich manganese-based positive electrode material, and the shell layer comprises a cationic disordered oxide; the cationic disordered oxide comprises a compound having a chemical composition shown in Formula 1,
[0118] Li z A x B 1-x O 2-y Dy Formula 1
[0119] In formula 1, 0.90≤x<1.0, 0≤y≤0.2, 0.78<z<1.1, A includes Ni and Mn in a molar ratio of (0.6-1):1, B includes at least one of Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce, and D includes F and / or S;
[0120] In the X-ray diffraction spectrum of the cationic disordered oxide, there is a diffraction peak with 2θ of 63° to 66°, and the diffraction peak is a single peak without splitting.
[0121] Specifically, in an oxygen atmosphere, a lithium-rich manganese-based positive electrode material according to a set ratio is uniformly mixed with raw materials including a lithium source, a source A, a source B and a source D to obtain a mixed material; the mixed material is first sintered at a temperature of 300 to 400° C., and the heat preservation time is 3 to 8 hours; then the product obtained after the first sintering is second sintered at a temperature of 450 to 700° C., and the heat preservation time is 20 to 40 hours; during the sintering process, the raw materials including the lithium source, the source A, the source B and the source D undergo a chemical reaction, and the lithium-rich manganese-based positive electrode material is Cationic disordered oxides are generated in situ on the surface, so that the prepared composite positive electrode active material includes a core (lithium-rich manganese-based positive electrode material) and a shell (cationic disordered oxide) coated on at least a portion of the surface of the core; and the cationic disordered oxide includes a compound with a chemical composition shown in Formula 1, and forms a cationic disordered oxide with a special crystal structure under the above-mentioned special sintering conditions, that is, in the XRD spectrum of the cationic disordered oxide, there is a diffraction peak located at 2θ of 63° to 66°, and the diffraction peak is a single peak without splitting.
[0122] Illustratively, the first sintering temperature is 300° C., 320° C., 340° C., 360° C., 380° C. or 400° C.; and the holding time is 3 h, 4 h, 5 h, 6 h, 7 h or 8 h.
[0123] Exemplarily, the second sintering temperature is 450°C, 475°C, 500°C, 525°C, 550°C, 575°C, 600°C, 625°C, 650°C, 675°C or 700°C; and the holding time is 20h, 25h, 30h, 35h or 40h.
[0124] The definition of the oxygen atmosphere in the present invention is consistent with that in the method for preparing the composite positive electrode active material of the second aspect above, and will not be elaborated here.
[0125] The definition of the mixing method in the present invention is consistent with the definition in the preparation method of the composite positive electrode active material in the second aspect above, and will not be elaborated here.
[0126] It should be noted that during the first sintering, the temperature is raised from room temperature to the temperature required for the first sintering; after the first sintering is completed, the temperature is directly raised to the temperature required for the second sintering for the second sintering.
[0127] The present invention does not specifically limit the heating rates during the first sintering and the second sintering, and a suitable heating rate may be selected according to actual conditions. For example, the heating rate may be 2 to 10° C. / min.
[0128] The definitions of the lithium-rich manganese-based positive electrode material, lithium source, source A, source B and source D in the present invention are consistent with those in the preparation method of the composite positive electrode active material of the second aspect above, and are not repeated here.
[0129] The present invention does not specifically limit the molar ratio of the lithium source, source A, source B, and source D. It is only necessary that the chemical composition of the prepared cationic disordered oxide satisfies Formula 1 and that there is an unsplit single peak at 2θ of 63° to 66° in its X-ray diffraction spectrum.
[0130] The present invention does not specifically limit the mass ratio of the lithium-rich manganese-based positive electrode material to the raw materials including the lithium source, A source, B source and D source; further, by controlling the mass ratio between the lithium-rich manganese-based positive electrode material and the raw materials, the mass ratio of the cationic disordered oxide to the lithium-rich manganese-based positive electrode material in the prepared composite positive electrode active material can be (0.5-3):100.
[0131] The preparation method of the composite positive electrode active material in the present invention is to mix and sinter the lithium-rich manganese-based positive electrode material with raw materials including a lithium source, a source A, a source B, and a source D, and under special sintering conditions, the lithium source, the source A, the source B, and the source D react to generate a cationic disordered oxide in situ on the surface of the lithium-rich manganese-based positive electrode material. The material has a chemical composition shown in Formula 1, and in its XRD spectrum, there is a single peak without splitting at 2θ of 63° to 66°, which indicates that the material has both a layered structure and a spinel structure. The cationic disordered oxide is coated on the surface of the lithium-rich manganese-based positive electrode material, which can effectively improve the compatibility of the shell and the core, thereby improving the migration efficiency of lithium ions. The coating layer can also effectively inhibit the occurrence of side reactions between the lithium-rich manganese-based positive electrode material and the electrolyte, thereby inhibiting the escape of lattice oxygen and improving the structural stability of the positive electrode material; the cationic disordered oxide can also participate in the electrochemical reaction during the charge and discharge process, improve the discharge capacity of the positive electrode material, and effectively reduce the loss of energy density. At the same time, the spinel structure can form interconnected three-dimensional ion diffusion channels, which is not only conducive to the deintercalation of lithium ions, but also can reduce the electrostatic repulsion during lithium deintercalation. Under high voltage, its lattice expansion and volume strain are small, and it has high structural stability; the two work together to effectively improve the lithium ion transmission efficiency and structural stability of the positive electrode active material. In addition, the relative content of nickel and manganese in the cationic disordered oxide is relatively appropriate, which can effectively avoid the problem of too much spinel structure caused by too little nickel and too much manganese, and the problem of dislocation of the crystal structure caused by too much nickel and too little manganese, thereby making the cationic disordered oxide have both good electrochemical properties and structural stability.
[0132] Therefore, the composite positive electrode active material prepared by the above preparation method can effectively improve the first coulombic efficiency, cycle performance and rate performance of the battery.
[0133] In a specific embodiment, the lithium-rich manganese-based positive electrode material is prepared by the following method:
[0134] The raw materials including nickel manganese precursor, lithium source, M source and N source are mixed to obtain a mixed material; the mixed material is sintered at 700-1100° C. for 10-24 hours in an oxygen atmosphere to obtain a lithium-rich manganese-based positive electrode material.
[0135] The lithium-rich manganese-based positive electrode material prepared by the above preparation method is doped with M element (at least one of Na, Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce) and N element (at least one of S, F, and P), thereby further improving the structural stability of the lithium-rich manganese-based positive electrode material.
[0136] Exemplarily, the sintering temperature is 700°C, 800°C, 900°C, 1000°C or 1100°C; and the holding time is 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.
[0137] The definitions of the nickel-manganese precursor, lithium source, M source and N source in the present invention are consistent with those in the preparation method of the composite positive electrode active material of the second aspect above, and are not elaborated here.
[0138] The present invention does not specifically limit the molar ratio of the nickel-manganese precursor material, the lithium source, the M source and the N source; further, the prepared lithium-rich manganese-based positive electrode material can satisfy Formula 2 by controlling the molar ratio between the four.
[0139] The present invention does not impose any specific limitation on the heating rate during the sintering process, and a suitable heating rate may be selected according to actual conditions, for example, the heating rate may be 2 to 10° C. / min.
[0140] The fourth aspect of the present invention provides a positive electrode sheet, which comprises the composite positive electrode active material of the first aspect, or the composite positive electrode active material prepared by the preparation method of the second aspect, or the composite positive electrode active material prepared by the preparation method of the third aspect. Therefore, the positive electrode sheet is used in a lithium-ion battery to effectively improve the first coulombic efficiency, cycle performance and rate performance of the battery.
[0141] It can be understood that the positive electrode sheet also includes a positive electrode current collector and a positive electrode active layer. The positive electrode active layer is arranged on at least a portion of the surface of the positive electrode current collector; the positive electrode active layer includes the above-mentioned composite positive electrode active material.
[0142] The present invention does not specifically limit the type of the positive electrode current collector, and a conventional current collector in the art may be used, for example, aluminum foil may be used as the positive electrode current collector.
[0143] Furthermore, the positive electrode active layer also includes a binder and a conductive agent.
[0144] The present invention does not specifically limit the types of the binder and the conductive agent, and conventional materials in the art may be used. For example, the binder may include at least one of polyvinylidene fluoride (PVDF), lithium polyacrylate (LiPAA) and polyvinyl acid (PAA); the conductive agent may include at least one of carbon black, graphite, acetylene black, Ketjen black, graphene and carbon nanotubes.
[0145] The present invention does not impose any specific restrictions on the mass ratio of the composite positive electrode active material, the binder and the conductive agent in the positive electrode active layer, and a suitable mass ratio can be selected according to actual needs.
[0146] The present invention does not specifically limit the preparation method of the positive electrode sheet, and the positive electrode sheet can be prepared by conventional methods in the art.
[0147] The fifth aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising the composite positive electrode active material of the first aspect, or the composite positive electrode active material prepared by the preparation method of the second aspect, or the composite positive electrode active material prepared by the preparation method of the third aspect, or the positive electrode sheet of the fourth aspect. Therefore, the lithium ion battery has a high first coulombic efficiency, cycle performance and rate performance.
[0148] The present invention does not specifically limit the preparation method of the battery. For example, the positive electrode sheet, the separator and the negative electrode sheet are wound or stacked to obtain a bare cell, the bare cell is packaged, and the battery is obtained after drying, liquid injection, shelving, formation and secondary sealing.
[0149] It can be understood that a lithium-ion battery also includes a negative electrode sheet, a separator and an electrolyte.
[0150] The present invention does not specifically limit the composition of the negative electrode sheet. In one embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least a portion of the surface of the negative electrode current collector; the negative electrode active layer includes a negative electrode active material, a binder and a conductive agent.
[0151] The present invention does not specifically limit the type of negative electrode current collector, and conventional current collectors in the art may be used, for example, copper foil may be used as the negative electrode current collector.
[0152] The present invention does not specifically limit the type of negative electrode active material, and conventional materials in the art may be used. For example, it may include carbon negative electrode active materials and / or silicon negative electrode active materials, wherein the carbon negative electrode active material includes at least one of natural graphite, artificial graphite, hard carbon, soft carbon, and carbon black; the silicon negative electrode active material includes at least one of elemental silicon, silicon-based composite materials, and silicon alloys.
[0153] The present invention does not specifically limit the type of binder, and conventional materials in the art may be used, for example, at least one of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and nitrile rubber (NBR).
[0154] The present invention does not specifically limit the type of the conductive agent, and conventional materials in the art may be used, for example, at least one of acetylene black, Ketjen black, graphite, graphene, and carbon nanotubes.
[0155] The present invention does not specifically limit the mass content of the negative electrode active material, the binder and the conductive agent in the negative electrode active layer, and a suitable mass ratio can be selected according to actual needs.
[0156] Hereinafter, the composite positive electrode active material provided by the present invention is described in detail through specific embodiments.
[0157] Example 1
[0158] 1) Li 1.36 (Ni 0.32 Mn 0.68 ) 0.995 Nb 0.005 O 2.36 Based on the stoichiometric ratio, lithium salt, Nb2O5 and nickel-manganese precursor material (Ni 0.32 Mn 0.68 (OH)2) are mixed uniformly to obtain a mixed material; the mixed material is placed in an atmosphere box furnace, heated to 900°C at 2°C / min in an air atmosphere, and sintered at this temperature for 15 hours; after cooling, the mixed material is crushed and sieved to obtain the lithium-rich manganese-based positive electrode material of this embodiment;
[0159] 2) According to a mass ratio of 1:100, the coating precursor and the lithium-rich manganese-based positive electrode material are mixed evenly, and the coating precursor includes a nickel-manganese precursor (Ni 0.5 Mn 0.5 (OH)2), LiCO3, LiF and AlF3, and the molar ratio of Li, Ni, Mn, Al, O and F is 0.97:0.495:0.495:0.01:1.97:0.03; after being evenly mixed, the mixture is placed in an atmosphere box furnace, and the temperature is increased to 300°C at 2°C / min in an air atmosphere for the first sintering, and the temperature is kept at this temperature for 5h; then the temperature is increased to 480°C at 2°C / min for the second sintering, and the temperature is kept at this temperature for 25h, and the mixture is cooled to room temperature and then crushed and sieved to obtain the composite positive electrode active material of this embodiment;
[0160] The composite positive electrode active material comprises a core lithium-rich manganese-based positive electrode material and a coating layer of cationic disordered oxide coated on the surface of the core; the chemical composition of the cationic disordered oxide is Li 0.97 Ni 0.495 Mn 0.495 Al 0.01 O 1.97 F 0.03 The cationic disordered oxide was subjected to XRD test. In its X-ray diffraction pattern, there was a diffraction peak with 2θ of 63° to 66°, and the diffraction peak was a single peak without splitting.
[0161] Example 2
[0162] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 2), the mass ratio of the coating precursor to the lithium-rich manganese-based positive electrode material is 0.5:100, and the rest remains unchanged.
[0163] Example 3
[0164] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 2), the mass ratio of the coating precursor to the lithium-rich manganese-based positive electrode material is 2:100, and the others remain unchanged.
[0165] Example 4
[0166] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 2), the mass ratio of the coating precursor to the lithium-rich manganese-based positive electrode material is 3:100, and the other factors remain unchanged.
[0167] Example 5
[0168] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 2), the coating precursor includes a nickel-manganese precursor Ni 0.45 Mn 0.55 (OH)2, LiCO3, LiF and AlF3, and the molar ratio of Li, Ni, Mn, Al, O and F is 0.87:0.455:0.545:0.01:1.97:0.03, and the others remain unchanged;
[0169] The chemical composition of the cationic disordered oxide in the prepared composite positive electrode active material is Li 0.87 Ni 0.445 Mn 0.545 Al 0.01 O 1.97 F 0.03 The cationic disordered oxide was subjected to XRD test. In its X-ray diffraction pattern, there was a diffraction peak with 2θ of 63° to 66°, and the diffraction peak was a single peak without splitting.
[0170] Example 6
[0171] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 2), the coating precursor includes a nickel-manganese precursor Ni 0.4 Mn 0.6 (OH)2, LiCO3, LiF and MgF2, and the molar ratio of Li, Ni, Mn, Mg, O and F is 0.792:0.396:0.594:0.01:1.98:0.02, and the others remain unchanged;
[0172] The chemical composition of the cationic disordered oxide in the prepared composite positive electrode active material is Li 0.792 Ni 0.396 Mn 0.594 Mg 0.01 O 1.98 F 0.02The cationic disordered oxide was subjected to XRD test. In its X-ray diffraction pattern, there was a diffraction peak with 2θ of 63° to 66°, and the diffraction peak was a single peak without splitting.
[0173] Example 7
[0174] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 2), the coating precursor includes a nickel-manganese precursor Ni 0.5 Mn 0.5 (OH)2, LiCO3, LiF, AlF3 and MoO3, and the molar ratio of Li, Ni, Mn, Al, Mo, O and F is 0.94:0.49:0.49:0.01:0.01:1.97:0.03, and the others remain unchanged;
[0175] The chemical composition of the cationic disordered oxide in the prepared composite positive electrode active material is Li 0.94 Ni 0.4 9Mn 0.49 Al 0.01 Mo 0.01 O 1.97 F 0.03 The cationic disordered oxide was subjected to XRD test. In its X-ray diffraction pattern, there was a diffraction peak with 2θ of 63° to 66°, and the diffraction peak was a single peak without splitting.
[0176] Example 8
[0177] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 2), the coating precursor includes a nickel-manganese precursor Ni 0.5 Mn 0.5 (OH)2, LiCO3, LiF, AlF3 and ZrO2, and the molar ratio of Li, Ni, Mn, Al, Zr, O and F is 0.96:0.49:0.49:0.01:0.01:1.97:0.03, and the others remain unchanged;
[0178] The chemical composition of the cationic disordered oxide in the prepared composite positive electrode active material is Li 0.96 Ni 0.4 9Mn 0.49 Al 0.01 Zr 0.01 O 1.97 F 0.03 The cationic disordered oxide was subjected to XRD test. In its X-ray diffraction pattern, there was a diffraction peak with 2θ of 63° to 66°, and the diffraction peak was a single peak without splitting.
[0179] Example 9
[0180] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 2), the coating precursor includes a nickel-manganese precursor Ni 0.5 Mn 0.5 (OH)2, LiCO3, LiF and WO3, and the molar ratio of Li, Ni, Mn, W, O, F is 0.92:0.49:0.49:0.02:1.98:0.02, and the others remain unchanged;
[0181] The chemical composition of the cationic disordered oxide in the prepared composite positive electrode active material is Li 0.92 Ni 0.4 9Mn 0.49 W 0.02 O 1.98 F 0.02 The cationic disordered oxide was subjected to XRD test. In its X-ray diffraction pattern, there was a diffraction peak with 2θ of 63° to 66°, and the diffraction peak was a single peak without splitting.
[0182] Example 10
[0183] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 1), Li 1.32 (Ni 0.35 Mn 0.65 ) 0.985 Sb 0.015 O 2.32 Based on the stoichiometric ratio, lithium salt, Sb2O5 and nickel manganese precursor (nickel manganese hydroxide Ni 0.35 Mn 0.65 (OH)2) are mixed evenly to obtain a mixed material; the mixed material is placed in an atmosphere box furnace, heated to 920°C at a heating rate of 5°C / min in an air atmosphere, and sintered for 15 hours to prepare the lithium-rich manganese-based positive electrode material of this embodiment.
[0184] Embodiment 11
[0185] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 1), Li 1.34 (Ni 0.32 Mn 0.68 ) 0.995 Mg 0.005 O 2.34 F 0.01 Based on the stoichiometric ratio, lithium salt, MgF2 and nickel-manganese precursor material (Ni 0.32 Mn 0.68(OH)2) is mixed evenly to obtain a mixed material; the mixed material is placed in an atmosphere box furnace, the temperature is increased to 900°C at 2°C / min in an air atmosphere, and the mixture is sintered for 15 hours to prepare the lithium-rich manganese-based positive electrode material of this embodiment.
[0186] Example 12
[0187] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 2), the mass ratio of the coating precursor to the lithium-rich manganese-based positive electrode material is 4:100.
[0188] Example 13
[0189] 1) Li 1.36 (Ni 0.32 Mn 0.68 ) 0.995 Nb 0.005 O 2.36 Based on the stoichiometric ratio, lithium salt, Nb2O5 and nickel-manganese precursor material (Ni 0.32 Mn 0.68 (OH)2) are mixed uniformly to obtain a mixed material; the mixed material is placed in an atmosphere box furnace, heated to 900°C at 2°C / min in an air atmosphere, and sintered at this temperature for 15 hours; after cooling, the mixed material is crushed and sieved to obtain the lithium-rich manganese-based positive electrode material of this embodiment;
[0190] 2) will include nickel manganese precursor (Ni 0.5 Mn 0.5 (OH)2), LiCO3, LiF and AlF3 are mixed evenly to obtain a first raw material, in which the molar ratio of Li, Ni, Mn, Al, O and F is 0.97:0.495:0.495:0.01:1.97:0.03; the first raw material is placed in an atmosphere box furnace, and a first sintering is performed in an air atmosphere, the heating rate in the first sintering is 2°C / min, the sintering temperature is 300°C, and the holding time is 4h; then the temperature of the box furnace is increased to 470°C at a heating rate of 2°C / min, the holding time is 30h, and the cationic disordered oxide of the present embodiment is obtained after being cooled to room temperature and crushed and sieved; the chemical composition of the cationic disordered oxide is Li 0.97 Ni 0.495 Mn 0.495 Al 0.01 O 1.97 F 0.03 ; The cationic disordered oxide was subjected to an XRD test, and in its X-ray diffraction pattern, there was a diffraction peak with a 2θ value of 63° to 66°, and the diffraction peak was a single peak without splitting;
[0191] 3) According to a mass ratio of 1:100, the cationic disordered oxide prepared above and the lithium-rich manganese-based positive electrode material are mixed evenly to obtain a second raw material; the second raw material is placed in an atmosphere box furnace, and the temperature is increased to 300°C at 5°C / min in an air atmosphere for a third sintering, and the heat preservation time is 6 hours. After cooling, it is crushed and sieved to obtain the composite positive electrode active material of this embodiment.
[0192] Embodiment 14
[0193] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 1), Li 1.61 (Ni 0.2 Mn 0.8 ) 0.995 Nb 0.005 O 2.61 Based on the stoichiometric ratio, lithium salt, Nb2O5 and nickel-manganese precursor (Ni 0.2 Mn 0.8 (OH)2) are mixed evenly to obtain a mixed material and sintered, and the sintering conditions remain unchanged.
[0194] Embodiment 15
[0195] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 1), Li 1.11 (Ni 0.45 Mn 0.55 ) 0.995 Nb 0.005 O 2.11 Based on the stoichiometric ratio, lithium salt, Nb2O5 and nickel-manganese precursor (Ni 0.45 Mn 0.55 (OH)2) are mixed evenly to obtain a mixed material and sintered, and the sintering conditions remain unchanged.
[0196] Example 16
[0197] The preparation method of the composite positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 1), Li 1.47 (Ni 0.32 Mn 0.68 ) 0.93 Nb 0.07 O 2.47 Based on the stoichiometric ratio, lithium salt, Nb2O5 and nickel manganese precursor (nickel manganese hydroxide Ni 0.32 Mn 0.68 (OH)2) are mixed evenly and sintered, and the sintering conditions remain unchanged.
[0198] Comparative Example 1
[0199] The preparation method of the composite positive electrode active material in this comparative example is basically the same as that in Example 1, except that the lithium-rich manganese-based positive electrode material is not subjected to any coating treatment.
[0200] Comparative Example 2
[0201] The preparation method of the composite positive electrode active material in this comparative example is basically the same as that in Example 1, except that, in step 2), the coating precursor and the lithium-rich manganese-based positive electrode material are evenly mixed and placed in an atmosphere box furnace, and the temperature is increased to 500°C at 2°C / min in an air atmosphere, and sintered for 35 hours to obtain the composite positive electrode active material in this comparative example.
[0202] Comparative Example 3
[0203] The preparation method of the composite positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 2), the coating precursor includes a nickel-manganese precursor (Ni 0.6 Mn 0.4 (OH)2), Li2CO3, LiF and AlF3, and the molar ratio of Li, Ni, Mn, Al, O and F is 0.996:0.588:0.392:0.02:1.8:0.2, and the others remain unchanged;
[0204] The chemical formula of the cationic disordered oxide in the prepared composite positive electrode active material is Li 0.996 Ni 0.588 Mn 0.392 Al 0.02 O 1.8 F 0.2 .
[0205] Comparative Example 4
[0206] The preparation method of the composite positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 2), the coating precursor includes a nickel-manganese precursor (Ni 0.3 Mn 0.7 (OH)2), Li2CO3, LiF and MgF2, and the molar ratio of Li, Ni, Mn, Mg, O and F is 0.594:0.297:0.693:0.01:1.98:0.02, and the others remain unchanged;
[0207] The chemical formula of the cationic disordered oxide in the prepared composite positive electrode active material is Li 0.594 Ni 0.297 Mn 0.693 Mg 0.01 O 1.98 F 0.02 .
[0208] Comparative Example 5
[0209] The preparation method of the composite positive electrode active material in this comparative example is different from that in Example 13 in that the cationic disordered oxide is different. Specifically, the lithium-rich manganese-based positive electrode material is mixed with the high-entropy cationic disordered oxide Li(Mn 0.2 Ni 0.2 Fe 0.2 Ti 0.2 Nb 0.2 )O2 mixed powder (the mass ratio of lithium-rich manganese-based positive electrode material to high-entropy cationic disordered oxide is 100:1) is placed in a ball mill for mechanical ball milling mixing, the ball milling speed is 300 rpm / min, the mass ratio of the mixed powder to the ball milling beads is 1:10, and the ball milling time is 2 h; the mixed powder after ball milling is transferred to a tubular furnace and sintered at 700 ° C for 4 h to obtain the composite positive electrode active material of this comparative example;
[0210] The high entropy cation disordered oxide Li(Mn 0.2 Ni 0.2 Fe 0.2 Ti 0.2 Nb 0.2 )O2 was tested by XRD. In its X-ray diffraction pattern, there was no diffraction peak with 2θ of 63° to 66°, such as Figure 5 shown.
[0211] Comparative Example 6
[0212] The preparation method of the composite positive electrode active material in this comparative example is different from that in Example 1 in that the cationic disordered oxide is different. Specifically, the lithium-rich manganese-based positive electrode material and the cationic disordered material Li2Mn 2 / 3 Nb 1 / 3 O2F was mixed evenly in a mass ratio of 100:1, placed in a muffle furnace, and sintered at 400-700°C for 8h; the sintered product was crushed to obtain the positive electrode active material of this comparative example;
[0213] The cation disordered material Li2Mn in this comparative example 2 / 3 Nb 1 / 3 O2F was tested by XRD. In its X-ray diffraction pattern, there was no diffraction peak with 2θ of 63° to 66°. Figure 5 shown.
[0214] Test example
[0215] 1. The activity of the composite positive electrode prepared in the above Example 1 and Comparative Example 1 was tested using a scanning electron microscope (SEM) of SU 8010 of Hitachi, Japan. The test results are shown in Figure 1 and Figure 2 .
[0216] Figure 1 is a SEM image of the composite positive electrode active material in Example 1, Figure 2 is a SEM image of the composite positive electrode active material in Comparative Example 1. Figure 1 and Figure 2 It can be seen that, compared with the lithium-rich manganese-based positive electrode material in Comparative Example 1 that has not been treated in any way, the composite positive electrode active material in Example 1 has an obvious coating formed on its surface.
[0217] 2. The cationic disordered oxides prepared in the above examples and comparative examples were subjected to XRD testing to observe whether there was a single peak without splitting in the 2θ range of 63° to 66° in the XRD spectrum. The test results are shown in Tables 1 and Figure 3-Figure 5 .
[0218] Figure 3 The cationic disordered oxide in Example 1 and the typical ternary layered LiNi 0.5 Mn 0.5 O2 and typical spinel LiNi 0.5 Mn 1.5 Comparison of local XRD diffraction peaks of O4 at 2θ of 63°~66°, Figure 3 In the figure, curve a is a typical spinel structure of LiNi 0.5 Mn 1.5 The local XRD diffraction curve of O4 at 2θ of 63°~66°, curve b is a typical layered structure of LiNi 0.5 Mn 0.5 The local XRD diffraction curve of O2 at 2θ of 63° to 66°, and the c curve is the local XRD diffraction curve of the cationic disordered oxide in Example 1 at 2θ of 63° to 66°. Figure 3 It can be seen that the typical layered structure of LiNi 0.5 Mn 0.5 O2 has two peaks at 2θ of 63°~66°, indicating that it has a complete layered structure; LiNi with a typical spinel structure 0.5 Mn 1.5 The characteristic peak of O4 at 2θ of 63°~66° is a sharp split peak, indicating that it has a good spinel structure and high crystallinity; while the characteristic peak of the cationic disordered oxide synthesized in Example 1 at 2θ of 63°~66° is a single peak without splitting, presenting a steamed bun shape, indicating that its crystallinity is slightly lower and the internal crystal is not a single layered or spinel structure.
[0219] Figure 4 The cationic disordered oxide in Comparative Example 2 and the typical ternary layered LiNi 0.5 Mn 0.5 O2 and typical spinel LiNi 0.5 Mn 1.5Comparison of local XRD diffraction peaks of O4 at 2θ of 63°~66°, Figure 4 In, by Figure 2 It can be seen that curve a is a typical spinel structure of LiNi 0.5 Mn 1.5 The local XRD diffraction curve of O4 at 2θ of 63°~66°, curve b is a typical layered structure of LiNi 0.5 Mn 0.5 The c curve is the local XRD diffraction curve of O2 at 2θ of 63° to 66°, and the c curve is the local XRD diffraction curve of the cationic disordered oxide in Comparative Example 2 at 2θ of 63° to 66°. Figure 4 In the comparative example 2, the cationic disordered oxide synthesized has a split diffraction peak at 2θ of 63° to 66°, and there is also a heterogeneous phase peak, indicating that the synthesized cationic disordered oxide contains a heterogeneous phase and the phase purity is not high.
[0220] Figure 5 The cationic disordered oxides in Comparative Examples 5 and 6 and the typical ternary layered LiNi 0.5 Mn 0.5 O2 and typical spinel LiNi 0.5 Mn 1.5 Comparison of local XRD diffraction peaks of O4 at 2θ of 63°~66°, Figure 5 In the figure, curve a is a typical spinel structure of LiNi 0.5 Mn 1.5 The local XRD diffraction curve of O4 at 2θ of 63°~66°, curve b is a typical layered structure of LiNi 0.5 Mn 0.5 The c curve is the local XRD diffraction curve of O2 at 2θ of 63°~66°, the c curve is the local XRD diffraction curve of the cationic disordered oxide in comparative example 5 at 2θ of 63°~66°, and the d curve is the local XRD diffraction curve of the cationic disordered oxide in comparative example 6 at 2θ of 63°~66°. Figure 5 In the comparative examples 5 and 6, the cationic disordered oxides synthesized have no diffraction peak at 2θ of 63° to 66°, indicating that the synthesized cationic disordered oxides do not have a layered and spinel composite structure.
[0221] 3. The composite positive electrode active materials prepared in the above embodiments and comparative examples are made into button batteries, comprising the following steps:
[0222] The composite positive electrode active material prepared above was mixed with a binder PVDF and a conductive agent Super-P at a mass ratio of 90:5:5, and was added to N-methylpyrrolidone for uniform dispersion to obtain a positive electrode active slurry; the positive electrode active slurry was coated on one surface of an aluminum foil, dried at 120°C, rolled, and punched to prepare a positive electrode sheet with a diameter of 13 mm, and the surface density of the positive electrode sheet was 12 mg / cm 2 , compacted density is 2.8mg / cm 3 In an argon-filled glove box, a lithium sheet was used as the negative electrode, a polypropylene microporous membrane (Celgard2400) was used as the separator, and an electrolyte was used to assemble a 2032-type button cell; the lithium salt in the electrolyte was lithium hexafluorophosphate (LiPF6) with a concentration of 1M, and the solvent was ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1.
[0223] At 25°C, the 2032 button cell prepared above was subjected to the following electrochemical performance tests using the Xinwei battery testing system:
[0224] 1) First Coulombic efficiency
[0225] The charge and discharge voltage window is 2.5V~4.55V. After the assembled battery has been at rest for 5h, it is charged to 4.55V at a constant current of 0.2C, and charged to a cut-off current of 0.05C at a constant voltage at 4.55V. After resting for 5min, it is discharged to 2.5V at a constant current of 0.2C (the charge and discharge current density of 1C is 230mA / g) to obtain the first charge and discharge specific capacity. The first coulombic efficiency (%) of the battery = (first discharge specific capacity / first charge specific capacity) × 100%.
[0226] 2) Cycle performance
[0227] The charge and discharge voltage window is 2.5V~4.55V. After the battery has tested the first cycle discharge capacity, it is charged to 4.55V at a constant current of 1C, and then charged at a constant voltage at 4.55V to a cut-off current of 0.05C. After resting for 5 minutes, it is discharged to 2.5V at a constant current of 1C, and the discharge capacity is recorded as C0. According to the above-mentioned charge and discharge mechanism, it is cycled 100 times, and the discharge capacity after the cycle is recorded as C1; then the cycle capacity retention rate (%) = (C1 / C0) × 100%.
[0228] 3) Rate performance
[0229] After the assembled battery has been stationary for 5 hours, it is charged to 4.55V at a constant current of 0.2C, charged to a cutoff current of 0.05C at a constant voltage at 4.55V, and discharged to 2.5V at a constant current of 0.2C after being stationary for 5 minutes. This cycle is repeated 3 times to obtain the discharge capacity after three discharges, and the average value is taken and recorded as C2; then it is charged to 4.55V at a constant current of 1C, charged to a cutoff current of 0.05C at 4.55V, and discharged to 2.5V at a constant current of 1C after being stationary for 5 minutes. This cycle is repeated 3 times to obtain the discharge capacity after three discharges, and the average value is taken and recorded as C3; then the rate performance (%) = (C3 / C2)×100%.
[0230] The test results are shown in Table 1 and Figure 6-Figure 9 .
[0231] Figure 6 is a charge and discharge curve diagram of the battery in Example 1 at 1C; Figure 7 is a charge and discharge curve diagram of the battery in Example 3 at 1C; Figure 8 is a charge and discharge curve diagram of the battery in Example 14 at 1C; Fig. 9 This is a charge and discharge curve of the battery in Example 15 at 1C.
[0232] Table 1
[0233]
[0234]
[0235] From Table 1, we can see that:
[0236] Compared with Comparative Examples 1 to 6, the button cells in Examples 1 to 16 have higher first coulombic efficiency, cycle performance and rate performance; wherein the first coulombic efficiency of the button cell in Example 1 is 86.2%, and accordingly, its cycle capacity retention rate is 92.7%, and the rate performance is 96.5%, which is significantly higher than the battery performance in Comparative Examples 1 to 6. It can be seen that the composite positive electrode active material in the present invention can effectively improve the first coulombic efficiency, rate performance and cycle performance of the battery.
[0237] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite positive electrode active material, characterized in that: The composite positive electrode active material comprises a core and a shell layer covering at least a portion of the surface of the core; the core comprises a lithium-rich manganese-based positive electrode material, and the shell layer comprises a cationic disordered oxide; the cationic disordered oxide comprises a compound with a chemical composition shown in Formula 1, Li z A x B 1-x O 2-y D y Formula 1 In formula 1, 0.90≤x<1.0, 0≤y≤0.2, 0.78<z<1.1, A includes Ni and Mn in a molar ratio of (0.6-1):1, B includes at least one of Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce, and D includes F and / or S; In the X-ray diffraction spectrum of the cationic disordered oxide, there is a diffraction peak with 2θ of 63° to 66°, and the diffraction peak is a single peak without splitting.
2. The composite positive electrode active material according to claim 1, characterized in that: The mass ratio of the cationic disordered oxide to the lithium-rich manganese-based positive electrode material is (0.5-3):
100.
3. The composite positive electrode active material according to claim 1 or 2, characterized in that: The thickness of the shell layer is 5nm to 20nm.
4. The composite positive electrode active material according to any one of claims 1 to 3, characterized in that: The lithium-rich manganese-based positive electrode material includes a compound with a chemical composition shown in Formula 2, Li 1+m Ni a Mn b M c O 2+m-d N d Formula 2 In formula 2, 0.2≤m≤0.4, a+b+c=1, 0.42≤a / b≤0.67, 0≤c≤0.02, 0≤d≤0.02; M includes at least one of Na, Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce; and N includes at least one of S, F, and P.
5. A method for preparing the composite positive electrode active material according to any one of claims 1 to 4, characterized in that: The following steps are involved: In an oxygen atmosphere, a first raw material including a lithium source, a source A, a source B, and a source D is uniformly mixed and then sequentially subjected to a first sintering and a second sintering to obtain a cationic disordered oxide; wherein the temperature of the first sintering is 300 to 400° C., and the holding time is 2 to 4 hours; the temperature of the second sintering is 450 to 600° C., and the holding time is 10 to 40 hours; the cationic disordered oxide includes a compound with a chemical composition shown in Formula 1, Li z A x B 1-x O 2-y D y Formula 1 In formula 1, 0.90≤x<1.0, 0≤y≤0.2, 0.78<z<1.1, A includes Ni and Mn in a molar ratio of (0.6-1):1, B includes at least one of Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce, and D includes F and / or S; In the X-ray diffraction spectrum of the cationic disordered oxide, there is a diffraction peak with a 2θ of 63° to 66°, and the diffraction peak is a single peak without splitting; In an oxygen atmosphere, the second raw material including the cationic disordered oxide and the lithium-rich manganese-based positive electrode material is uniformly mixed and then subjected to a third sintering to obtain the composite positive electrode active material; wherein the temperature of the third sintering is 300-500° C. and the insulation time is 2-12 hours.
6. The method for preparing a composite positive electrode active material according to claim 5, characterized in that: The lithium-rich manganese-based positive electrode material is prepared by the following method: The raw materials including nickel manganese precursor, lithium source, M source and N source are mixed to obtain a mixed material; the mixed material is sintered at 700-1100° C. for 10-24 hours in an oxygen atmosphere to obtain the lithium-rich manganese-based positive electrode material.
7. A method for preparing the composite positive electrode active material according to any one of claims 1 to 4, characterized in that: The following steps are involved: In an oxygen atmosphere, a lithium-rich manganese-based positive electrode material is uniformly mixed with raw materials including a lithium source, a source A, a source B and a source D, and then a first sintering and a second sintering are performed in sequence to obtain a composite positive electrode active material; wherein the temperature of the first sintering is 300-400° C., and the insulation time is 3-8 hours; the temperature of the second sintering is 450-700° C., and the insulation time is 20-40 hours; The composite positive electrode active material comprises a core and a shell layer covering at least a portion of the surface of the core; the core comprises a lithium-rich manganese-based positive electrode material, and the shell layer comprises a cationic disordered oxide; the cationic disordered oxide comprises a compound with a chemical composition shown in Formula 1, Li z A x B 1-x O 2-y D y Formula 1 In formula 1, 0.90≤x<1.0, 0≤y≤0.2, 0.78<z<1.1, A includes Ni and Mn in a molar ratio of (0.6-1):1, B includes at least one of Mg, Sr, Y, Ti, Zr, Nb, Ta, Cr, Mo, W, Co, Al, Ga, Sn, Sb, Te, La, and Ce, and D includes F and / or S; In the X-ray diffraction spectrum of the cationic disordered oxide, there is a diffraction peak with 2θ of 63° to 66°, and the diffraction peak is a single peak without splitting.
8. The method for preparing a composite positive electrode active material according to claim 7, characterized in that: The lithium-rich manganese-based positive electrode material is prepared by the following method: The raw materials including nickel manganese precursor, lithium source, M source and N source are mixed to obtain a mixed material; the mixed material is sintered at 700-1100° C. for 10-24 hours in an oxygen atmosphere to obtain the lithium-rich manganese-based positive electrode material.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the composite positive electrode active material according to any one of claims 1 to 4, or the composite positive electrode active material prepared by the preparation method according to claim 5 or 6, or the composite positive electrode active material prepared by the preparation method according to claim 7 or 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite positive electrode active material according to any one of claims 1 to 4, or the composite positive electrode active material prepared by the preparation method according to claim 5 or 6, or the composite positive electrode active material prepared by the preparation method according to claim 7 or 8, or the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Lithium-rich manganese-based positive electrode material with multi-layer composite structure and preparation method of lithium-rich manganese-based positive electrode material
CN117199300A
Cited By
Composite positive electrode material and preparation method and application thereof
CN120319790A
Positive electrode active material and preparation method thereof
CN121331814A
Lithium-rich manganese-based positive electrode material with core-shell structure and preparation method of lithium-rich manganese-based positive electrode material
CN121726383A